IMPLEMENTASI PROGRAM PEMBANGUNAN INFRASTRUKTUR PERDESAAN (PPIP) DI KABUPATEN TEMANGGUNG TAHUN 2014 - Meida Anggraeni Setyowati; Endang Larasati (Dialogue : Jurnal Ilmu Administrasi Publik, 2019)
Rural Infrastructure Development Program (PPIP) strives to establish and improvethe quality of people's lives, either individually or in groups through participation insolving various problems related to poverty, women's empowerment and village leftbehind in an effort to improve the quality of life, independence and prosperity. Locationof Rural Infrastructure Development Program (PPIP) spreads in 29 provinces, targetinglocations follow the provisions Minister Decree of Public Works with Public WorksMinister's decision regarding the determination target villages of Rural InfrastructureDevelopment Program (PPIP). Which is basically establishes village recipients list ofprogram then called as Rural Target of Rural Infrastructure Development Program(PPIP). The purpose of this study is to describe and analyze the implementation of theRural Infrastructure Development Program (PPIP) in Temanggung District; andanalyzes factors that support and inhibit the success of the Rural InfrastructureDevelopment Program (PPIP) in TemanggungDistrict. The driving factors of this policyis good communication and disposition of Rural Infrastructure Development Program(PPIP) from implementor namely Public Works Department of Temanggung to the publicas the program implementers i.e. Getas rural communities. While the inhibiting factorsare affected by a lack of human resources i.e. the number of employees who areconsidered insufficient to handle the number of programs in a relatively time together.Another inhibiting factor is the structure of bureaucracy, namely the division of dutiesand functions of officials and employees with each other, cross over the fieldoftenoccurred. Besides that, the prominent barriers which felt by rural communities is basicusage per sub-district as the main indicator of the disbursement of funds by terms orgradual disbursement system. According to the name of this policy, namely RuralInfrastructure Development Program (PPIP), the basis for the disbursement of fundsshould be per village, so that the implementation of the program can be run moreeffectively.